Normative and Empirical Treatment of Intimate Partner Violence in Family Mediation Processes in Latin America: A Comparative Study with Projections for Chile (Justicia &Derecho, 2025)
This article it addresses the normative and empirical treatment given to intimate partner violence in family mediation processes in Latin America and the projections for Chile. Through a qualitative and comparative dogmatic methodology, the regulations, doctrine, jurisprudence and methodologies used in Argentina, Colombia and Chile are explored. The research reveals that, in some Latin American countries, intimate partner violence is recognized and addressed within the family mediation process. However, in Chile, this phenomenon has not been sufficiently regulated or considered within family mediation processes, which generates an invisibilization of violence, especially psychological and economic violence.
Keywords: Intimate partner violence; family mediation; normative treatment; empirical treatment